2019
DOI: 10.1002/joa3.12211
|View full text |Cite
|
Sign up to set email alerts
|

Troubleshooting in PM Leadless: How to manage an indissoluble knot

Abstract: A 77‐year‐old patient, with permanent atrial fibrillation, underwent successful Micra transcatheter pacing system (MTPS) implantation. Once begun the pull‐back of the tether, an increasing resistance was felt by the operator until complete blockage. A challenging recapture of MTPS into the delivery system was performed. The retrieved MTPS showed an indissoluble knot close to the docking button that blocked the running of the tether, and a long clot inside the delivery system. The new design of internal handle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…They implanted a leadless pacemaker in a 77-year-old man and experienced difficulty releasing the device and retracting the delivery due to a clot on the tether. Morani et al 7 reported a similar case; they discussed delivery system flushing and the design of the inner flushing tube system. Both reports did not mention coagulability.…”
Section: Discussionmentioning
confidence: 95%
“…They implanted a leadless pacemaker in a 77-year-old man and experienced difficulty releasing the device and retracting the delivery due to a clot on the tether. Morani et al 7 reported a similar case; they discussed delivery system flushing and the design of the inner flushing tube system. Both reports did not mention coagulability.…”
Section: Discussionmentioning
confidence: 95%
“… 21 , 22 Device release and delivery system retraction can be interrupted if a clot forms on the tether. This can either be operator-related where following the design of the inner flushing tube system of the LPM implantation device, a certain operator technique can reduce the clotting risk, 23 or case-by-case–related factors where preprocedural blood transfusion may increase blood viscosity, hence increasing clot formation. 24 On the other hand, our study shows that TV-VVI patients were more likely to undergo CIED revisions during the same admission in comparison to LPM.…”
Section: Discussionmentioning
confidence: 99%
“…Both approaches require femoral venous access with insertion of a TPS introducer sheath, but then diverge with regard to the specific tool employed to engage the TPS during the next step: the snare is advanced through either i) the integrated protectable sleeve of the TPS delivery catheter (as employed in our case series), or ii) a steerable sheath [10]. In using a steerable sheath, a short sheath (11)(12)(13)(14)(15)(16) is first inserted into the introducer sheath to prevent back bleeding, and a steerable sheath (for example, 8.5 Fr, Agilis NXT, Abbott Laboratories, Abbott Park, IL, USA) is inserted and advanced into the RV.…”
Section: Figure 3: Intracardiac Echocardiography (Ice)mentioning
confidence: 99%